Rapid diversity assessment of litter myxomycete assemblages in the upland and coastal terrains of San Fernando City, La Union, Philippines - RAMON CARLO BALAORO-BANZUELA; CHRISTIAN ELMARC OCENAR-BAUTISTA; DON ENRICO BUEBOS-ESTEVE; CELINE YSSABELL CLAUDIO-PARAGAS; JAMES EDUARD LIMBO-DIZON; NIKKI HEHERSON A. DAGAMAC (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Balaoro-Banzuela RC, Ocenar-Bautista CE, Buebos-Esteve DE, Claudio-Paragas CY, Limbo-Dizon JE, Dagamac NHA. 2023. Rapid diversity assessment of litter myxomycete assemblages in the upland and coastal terrains of San Fernando City, La Union, Philippines. Biodiversitas 24: 2877-2886. Over the past few years, increasing studies have been on diversity assessments of myxomycetes in the Philippines. Despite these, their utility as bioindicators to evaluate approaches for sustainable ecosystem management remains largely unexplored. Following the ridge-to-reef (R2R) approach, a comparative diversity assessment was conducted between the upland and coastal terrains of San Fernando City, La Union, Philippines. Aerial and ground litter were haphazardly collected and cultivated at ambient conditions using the moist chamber (MC) technique. MCs were highly productive, exhaustively yielding a total of 27 distinct species belonging to 10 different genera. Regarding abundance, 15 species were rare, and four were occasional, common, and abundant. Both species richness and occurrence of rare taxa were higher in the upland terrain than in the coastal terrain. However, several ?-diversity indices hinted at no significant difference in species diversity between terrains and substrates. At the community level, clustering analyses and other ?-diversity indices revealed that myxomycete assemblages were more similar in terrain than the substrate. This study implicates using myxomycetes as proxy biological models to reflect the ecological influences of plant heterogeneity and human-mediated disturbance. This allows its integration into local policymaking with adherence to R2R management.